Critical criminology today counter-hegemonic essays - Ruggiero, Vincenzo (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"What survives of the notions, principles and values of critical criminology? Faced with contexts that could not be more dramatically different to those fostering critical approaches to crime and its control, what is left of the radical theories and practical initiatives that characterized it in the 1970s? This book argues that critical criminology today can be reimagined if new concepts are elaborated which bring academic efforts close to the practices of social movements. Building on an original collection of anti-hegemonic essays focused on specific criminological areas, including femicide, organized crime, drug use, punishment, state-corporate terrorism and financial crime, this book identifies the radical potential inherent in the choice of areas, topics and variables that critical criminologists can address today. In discussing concepts of distance, power, mercy and troublemaking, this book considers the relationship between critical criminology, social justice and activism. An accessible and compelling read, this book will appeal to all those engaged with critical criminology, sociology, and cultural studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Critical criminology; SOCIAL SCIENCE / Criminology